Paenilamicin: Structure and Biosynthesis of a Hybrid Nonribosomal Peptide/Polyketide Antibiotic from the Bee Pathogen Paenibacillus larvae1. Issue 40 (30th July 2014) - Müller, Sebastian; Garcia‐Gonzalez, Eva; Mainz, Andi; Hertlein, Gillian; Heid, Nina C.; Mösker, Eva; van den Elst, Hans; Overkleeft, Herman S.; Genersch, Elke; Süssmuth, Roderich D.
Abstract The spore‐forming bacterium Paenibacillus larvae is the causative agent of American Foulbrood (AFB), a fatal disease of honey bees that occurs worldwide. Previously, we identified a complex hybrid nonribosomal peptide/polyketide synthesis (NRPS/PKS) gene cluster in the genome of P. larvae. Herein, we present the isolation and structure elucidation of the antibacterial and antifungal products of this gene cluster, termed paenilamicins. The unique structures of the paenilamicins give deep insight into the underlying complex hybrid NRPS/PKS biosynthetic machinery. Bee larval co‐infection assays reveal that the paenilamicins are employed by P. larvae in fighting ecological niche competitors and are not directly involved in killing the bee larvae. Their antibacterial and antifungal activities qualify the paenilamicins as attractive candidates for drug development.